The use of the Amplatzer Vascular Plug in the prevention of endoleaks during abdominal endovascular aneurysm repair: A systematic literature review on current applications. (August 2022) - Bracale, Umberto M; Petrone, Anna; Provenzano, Michele; Ielapi, Nicola; Ferrante, Liborio; Turchino, Davide; del Guercio, Luca; Pakeliani, David; Andreucci, Michele; Serra, Raffaele
Objectives: The Amplatzer Vascular Plug (AVP) is a vascular occlusion device designed to provide optimal embolization in several fields of the endovascular surgery. A full literature review was conducted to analyze AVPs in comparison with coils for the prevention of endoleaks during endovascular abdominal aortic aneurysm repair. Methods: A systematic review was designed under PRISMA statement guidelines for systematic reviews and meta-analyses. The results were updated with a subsequent electronic search using Medline and Scopus databases up to December 2019. Results: Eighteen articles making this comparison were found. In 79.7% of the cases, the target vessel was the internal iliac artery; in 1.6%, the common iliac artery; and in 16.7%, the inferior mesenteric artery. Risk of complications (buttock claudication, groin hematoma, endoleaks, and erectile dysfunction) after AVP was low. A cost comparison revealed that the mean cost for coils was around US$2262, while the average cost for the AVP was US$310. Conclusions: The AVP is an effective and safe device for occluding peripheral vessels, proved to have lower complications rates. Compared with coil embolization, the AVP technique is potentially associated with lower procedural costs.